PENATALAKSANAAN PADA PRIA USIA 53 TAHUN DENGAN DIABETES MELITUS TIPE 2 DAN TB PARU MELALUI PENDEKATAN DOKTER KELUARGA DI WILAYAH PUSKESMAS RAJABASA INDAH - Soetardi, Eriza Kultsum R; Mayasari, Diana (Medula, 2024)
Non-communicable diseases (NCDs) and other degenerative diseases are still a major national health problem in Indonesia. One of the NCDs that continues to increase in Indonesia is Diabetes Mellitus cases. Morbidity and mortality rates due to type 2 diabetes and tuberkulosis (TB) are increasing among people with type 2 diabetes. According to WHO data, people with type 2 diabetes have a three times higher chance of contracting tuberkulosis (TB) than people without the disease. The aim of the family approach in the treatment of pulmonary tuberkulosis in diabetes mellitus sufferers is to determine the clinical, psychological and psychosocial determinants that influence the family. By implementing comprehensive family doctor services that are based on evidence-based medicine and a patient-centered approach. A 53 year old patient, who is the head of a family with teenage children and a school member whose only income is from the wife of a trader at school, has complaints of a cough that has not healed since the last month accompanied by intermittent fever, itchy throat, decreased appetite, body weight, and tingling in the hands and feet with a history of suffering from diabetes mellitus for 15 years. The patient was found to be suffering from diabetes and a new case of pulmonary tuberkulosis. The patient has difficulty carrying out activities and needs the role of family such as the patient's wife and children to help heal the patient's condition. After the intervention, the patient's fasting blood sugar decreased, clinical symptoms improved, and the level of knowledge increased. The patient's diagnosis of a new case of pulmonary tuberkulosis with type 2 diabetes was made according to recommendations. After implementing the patient-centered approach, family approach intervention, the patient's level of knowledge changed. As a result of implementing a comprehensive management strategy led by a family doctor, patient and family understanding of type 2 diabetes mellitus and pulmonary TB has increased. So that from the results of this research and intervention, it is hoped that patients and families will receive comprehensive services both in terms of physical, psychological health and level of knowledge with changes in behavior in managing the patient's illness.